2022
DOI: 10.1186/s12958-022-00887-5
|View full text |Cite|
|
Sign up to set email alerts
|

EndMT: New findings on the origin of myofibroblasts in endometrial fibrosis of intrauterine adhesions

Abstract: Background Intrauterine adhesion (IUA) is one of the leading causes of infertility and the main clinical challenge is the high recurrence rate. The key to solving this dilemma lies in elucidating the mechanisms of endometrial fibrosis. The aim of our team is to study the mechanism underlying intrauterine adhesion fibrosis and the origin of fibroblasts in the repair of endometrial fibrosis. Methods Our experimental study involving an animal model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The current immunohistochemical findings revealed a significant increase of vimentin and α-SMA along with ovarian and oviduct fibrosis. Several studies considered vimentin and α-SMA as reliable fibrotic markers [42][43][44] . Mesenchymal myofibroblasts cells have an intermediate nature between fibroblasts and smooth muscle cells and they are the major cells responsible for the production of collagen, which leads to fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current immunohistochemical findings revealed a significant increase of vimentin and α-SMA along with ovarian and oviduct fibrosis. Several studies considered vimentin and α-SMA as reliable fibrotic markers [42][43][44] . Mesenchymal myofibroblasts cells have an intermediate nature between fibroblasts and smooth muscle cells and they are the major cells responsible for the production of collagen, which leads to fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin is strongly expressed in mesenchyme tissues, with weak to negative immunoexpression in epithelial cells, whereas α-SMA expression in the cytoplasm provides cellular contractility, which is intimately related with fibrosis [44] . Myofibroblasts generally vanish following effective tissue healing, but deregulation of normal repair mechanisms, such as chronic inflammation or oxidative stress in the tissue, can result in prolonged myofibroblasts activation leading to excess collagen production, which finally results in fibrosis [43] . The significant increase of hydroxyproline, a major component of collagen, in the presented work is in agreement with several studies that reported the correlation between fibrosis and hydroxyproline elevation [43,45] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblasts are increasingly recognized as playing a role in inflammation, [62] implicating that fibrosis and inflammation are closely intertwined, potentially through macrophages [47] . The epithelial‐to‐mesenchymal transition, in which epithelial cells lose their intercellular junctions and become migratory and invasive, is known to play a role in endometriosis through fibroblast activation [63–66] . In other diseases, chronic low‐grade inflammation is recognized as a precursor to fibrosis [54] and this may also be the case for endometriosis.…”
Section: Molecular Targets and Active Principles In Endometriosismentioning
confidence: 99%
“…Correction to: Reprod Biol Endocrinol 20, 9 (2022) https://doi.org/10.1186/s12958-022-00887-5 Following publication of the original article [1], the authors reported an error in Fig. 1.…”
mentioning
confidence: 99%